Nutrient utilization, ruminal microbial population and fermentation characteristics of West African Dwarf (WAD) rams fed ammonium sulphate fortified diets (2016)
The ruminal microbial population has enormous potential for fibre digestion. Microorganisms are responsible for breakdown of plant cell walls, fungi have better ability to attack lignocellulosic tissues for bacteria to act on it. Ammonium sulphate, a chemical compound that serves as a ready source of nitrogen and sulphur, plays important roles in enhancing rumen microbial activity. Therefore, the effects of ammonium sulphate fortification on rumen fermentation characteristics and microbial populations were evaluated. Sixteen (16) West African dwarf (WAD) rams weighing 12.8±0.12kg were assigned to diets containing 0g/100kg (control diet), 250g/100kg, 500g/100kg and 750g/100kg levels of ammonium sulphate (T1, T2, T3 and T4 respectively) in a completely randomized design, each ram fed 5% body weight of the diet and wilted guinea grass in a 60:40 ratio for 105 days. At the end of the feeding trial, the effects of the diets on rumen microbial population and fermentation characteristics of the rams were assessed. The fungi population in sheep fed ammonium sulphate fortified diets ranged from 3.37- 4.36 x 10(4) cfu/ml. Acetate, propionate and butyrate in the ammonium sulphate fortified diets ranged from 46.37 - 48.71, 29.41 - 33.25 and 21.00 - 24.75 mmole/100ml respectively. The acetate and butyrate of the ammonium sulphate fortified diets decreased with increasing inclusion levels of ammonium sulphate, while the propionate decreased. Results obtained showed that ammonia nitrogen, fungi, bacteria and acetate were 1.45ppm, 4.36 cfu/ml, 7.01 cfu/ml, 48.71 mmole/100ml respectively, and they were significantly (P<0.05) highest in rams fed diet fortified with 750g/100kg ammonium sulphate. Rams on control diet had significantly (P<0.05) higher values of protozoa, pH, acetate and butyrate (5.96 cfu/ml, 6.82, 48.71 mmole/100ml, 24.75 mmole/100ml) than rams on T2, T3 and T4 because the control diet is not fortified with ammonium sulphate. It was concluded that rams fed 750g/100kg of ammoniumsulphate had greater number of rumen microbes which resulted in higher microbial protein synthesis, hence improved performance and higher body weight gain.